Prediction of forming limit in DP590 steel sheet forming: An extended fracture criterion. (15th April 2016) - Ma, Bolin; Liu, Z.G.; Jiang, Zheng; Wu, Xiangdong; Diao, Keshan; Wan, Min
Abstract: In this paper, we propose an extended ductile fracture criterion to study forming limit of DP 590 steel sheet. This criterion involves two independent parameters, stress triaxiality η and Lode parameter μ base on continuum damage mechanics, and assume that the damaged and undamaged configuration obey same material plastic evolution law. Thereafter, the criterion is extended to sheet metal forming under plane stress assumption. The tensile tests and Nakajima tests are employed to investigate fracture mechanism and validate fracture criterion. The forming limit diagram (FLD) of DP590 steel sheet is obtained by Nakajima tests throughout fracture and necking features on the specimens, which represent the upper band and lower band of FLD respectively. The theoretical FLD are determined by proposed fracture criterion with left and right side of FLD respectively. The predicted FLD is in good agreement with the experimental determined FLD, which demonstrates the capability of forming limit prediction by current proposed fracture criterion. Graphical abstract: Highlights: A ductile fracture criterion was proposed to study forming limit of DP590 steel sheet. The criterion was extended to sheet metal forming with stress triaxiality and Lode parameter under plane stress assumption. The experimental FLD of DP590 steel was obtained throughout fracture and necking features. The theoretical predicted FLD shows good agreement with the experimental determined FLD for DP590 sheet metal.